MATERNAL AND NEONATAL SERUM COPPER LEVEL AT BIRTH - D.Froozani; K.Montazami; F.Ravasizadeh (Tehran University of Medical Sciences, 1978)
Total serum copper levels of 70 pregnant women hospitalized for delivery at Misaghieh (private), 90 at Farah (Public) Maternity Hospitals immediately after delivery and 27 non-pregnant women (Control) were measured. The copper level in the blood serum of umbilical cord of the newborn infants was also determined. The copper levels were significantly elevated in both pregnant groups as compared to the non-pregnant group. However, the copper level in the blood serum of the umbilical cord from the private group was significantly higher when compared to those from the public group. A significant correlation was found between the serum copper level of mothers and the cord blood in both, private and public groups.